Digital Banking, Digital Culture, Organizational Learning, Innovation, and Employee Performance - Mega Mahayani; Gede Sri Darma (Jurnal Manajemen, 2025)
This study explored the impact of digital disruption practices, particularly in the private banking sector (BPR), on employee performance. 124 BPR employees participated, with data collected through a questionnaire distributed via Google Forms. The data were analysed using Partial Least Squares (PLS) methodology. The findings revealed that nine out of ten tested hypotheses showed a positive and significant effect. However, the effect of Organizational Learning on Employee Performance, while positive, was not statistically significant. These results suggest that the digital transformation of the banking sector, particularly within BPR, should be implemented promptly as it offers long-term benefits. Additionally, such digitalisation efforts are expected to contribute significantly to financial inclusion and the development of the broader economic sector.